Community-based exercise for health promotion and secondary cancer prevention in Canada: protocol for a hybrid effectiveness-implementation study. Issue 9 (13th September 2019) - McNeely, Margaret L; Sellar, Christopher; Williamson, Tanya; Shea-Budgell, Melissa; Joy, Anil Abraham; Lau, Harold Y; Easaw, Jacob C; Murtha, Albert D; Vallance, Jeffrey; Courneya, Kerry; Mackey, John R; Parliament, Matthew; et al.
Abstract : Introduction: Cancer care has expanded from a disease-focused, survival-oriented model to an approach that now considers how survivors can live well in the aftermath of intensive therapy, where they may deal with significant changes to their bodies, mental health or emotional well-being. Research evidence supports the benefit of exercise during and following cancer treatments for cancer-related symptoms, physical functioning and fitness, and health-related quality of life. To move this efficacy evidence into practice, we designed and launched a 5-year study to evaluate the relative benefit from implementing a clinic-to-community-based cancer and exercise model of care. Methods and analysis: A hybrid effectiveness and implementation trial design is being used to evaluate the effectiveness of delivery of community-based exercise and to collect data on implementation of the programme. The study opened in January 2017, with estimated completion by January 2022. The programme will be delivered in seven cities across the province of Alberta, Canada, with sites including three academic institutions, six YMCA locations, Wellspring Edmonton and Calgary, and six municipal fitness centres. Participants are adult cancer survivors (n=2500) from all tumour groups and stages and at any time point along their cancer treatment trajectory, up to 3 years post treatment completion. Survivors take part in a minimum of 60 min of mild-to-moderate intensity full body exercise twice weekly for a 12-week period. The primary effectiveness outcome is the proportion of participants meeting or exceeding 150 min of moderate intensity exercise per week at 1-year follow-up. The Reach, Effectiveness, Adoption, Implementation and Maintenance (RE-AIM) framework will be utilised to capture individual-level and organizational-level impact of the exercise programme at 12 and 24 weeks and 1-year follow-up. The cohort of survivors participating in the study will allow for long-term (>5-year) evaluation of rates of cancer recurrence and secondary cancers beyond the funding period. Ethics and dissemination: The study was approved by the Health Research Ethics Board of Alberta. The study is funded by Alberta Innovates and the Alberta Cancer Foundation. The study will help to answer critical questions on the effectiveness of cancer-specific community-based exercise programming in both the short-term and the long-term. Collectively, the findings will help to inform the acceptability, adoption, feasibility, reach and sustainability of community-based exercise. Trial registration number: NCT02984163 ; Pre-results.